Prevention and treatment of atypical haemolytic uremic syndrome after kidney transplantation. (July 2016) - Okumi, Masayoshi; Tanabe, Kazunari
Abstract: Atypical haemolytic uraemic syndrome is a rare disorder characterized by an over‐activated, dysregulated alternative complement pathway due to genetic mutation and environmental triggers. Atypical haemolytic uraemic syndrome is a serious, life‐threatening disease characterized by thrombotic microangiopathy, which causes haemolytic anaemia, thrombocytopaenia, and acute renal failure. Since recurrences of atypical haemolytic uraemic syndrome frequently lead to end‐stage kidney disease even in renal allografts, kidney transplantation for patients with end‐stage kidney disease secondary to atypical haemolytic uraemic syndrome has long been contraindicated. However, over the past several years, advancements in the management of atypical haemolytic uraemic syndrome have allowed successful kidney transplantation in these patients. The key factor of this success is eculizumab, a humanized anti‐C5 monoclonal antibody, which inhibits terminal membrane‐attack complex formation and thrombotic microangiopathy progression. In the setting of kidney transplantation, there are different possible triggers of post‐transplant atypical haemolytic uraemic syndrome recurrence, such as brain‐death related injury, ischaemia–reperfusion injury, infections, the use of immunosuppressive drugs, and rejection. Principal strategies are to prevent endothelial damage that could potentially activate alternative complement pathway activation and subsequently lead to atypical haemolytic uraemic syndrome recurrence in kidney allograft. Published data shows that prophylactic eculizumab therapy is highly effective for the prevention of post‐transplant atypical haemolytic uraemic syndrome recurrence, and prompt treatment with eculizumab as soon as recurrence is diagnosed is important to maintain renal allograft function. Further study to determine the optimal dosing and duration of prophylactic therapy and treatment of post‐transplant atypical haemolytic uraemic syndrome recurrence is needed.